2010
DOI: 10.1111/j.1440-172x.2010.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Embodied reflection in practice—‘Touching the core of caring’

Abstract: Ranheim A, Kärner A, Arman M, Rehnsfeldt AW, Berterö C. International Journal of Nursing Practice 2010; 16: 241–247
Embodied reflection in practice—‘Touching the core of caring’ A study was performed with the aim of clarifying the integration of the caring act of touch with reflection on caring theory. Seven participant nurses in elderly care volunteered as ‘coresearchers’ and performed a caring act called Rhythmical Embrocation, together with reflective dialogues on caring theory. The project lasted for 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Touch in different forms is described as inevitable in the care of patients, and as an integration of physical, emotional and existential dimensions, which can relieve suffering and render a release from strain in contact with another human being. Examples can be found in the care of elderly persons , in palliative home‐care and also in acute‐care settings . Touch can also have negative effects or could generate ambivalent feelings .…”
Section: Introductionmentioning
confidence: 99%
“…Touch in different forms is described as inevitable in the care of patients, and as an integration of physical, emotional and existential dimensions, which can relieve suffering and render a release from strain in contact with another human being. Examples can be found in the care of elderly persons , in palliative home‐care and also in acute‐care settings . Touch can also have negative effects or could generate ambivalent feelings .…”
Section: Introductionmentioning
confidence: 99%
“…Ranheim et al (2010) found in a previous study how participating nurses, while giving touch, become more "aware" and described an expansion in their senses when they become more vulnerable and open in their encounters with their patients. During their training in TM, those experiences were not discussed.…”
Section: Results Discussionmentioning
confidence: 88%
“…During their training in TM, those experiences were not discussed. The importance of an emotional association in the encounter as an essence of caring was also described by Ranheim et al (2010). This emphasizes the importance of training nurses in TM, to become aware of what may happen during treatment, since for some this was a frightening experience in the beginning.…”
Section: Results Discussionmentioning
confidence: 99%
“…Some caring activities such as rhythmical embrocation (RE) can be used as an opening act of care: opening up for temporality. Performing RE was described as becoming relaxed in an integrated way, being calm, and allowing a sense of “being” and “presence” (Ranheim, Karner, Arman, Rehnsfedlt, & Bertero, ).…”
Section: Discussionmentioning
confidence: 99%